Nauji monokloniniai antikūnai žuvų alergenų nustatymui ir tyrimams - Sližienė, Aistė (Institutional Repository of Vilnius University, 2023)
Fish allergens (like β-parvalbumin, β-enolase) that are found in fish muscle can cause various symptoms for fish allergic patients. Recombinant fish allergens and allergen-specific monoclonal antibodies (MAbs) might be applied for development of immunoassays to detect fish allergen in food samples. In the current study, recombinant fish allergens and allergen-specific MAbs were investigated. A collection of recombinant allergens fused with maltose binding protein were produced in E. coli: 11 fish β-parvalbumins, common carp β-enolase and two α-parvalbumins (shark and chicken). For the first time, a recombinant β-enolase of common carp was generated and identified as a new fish allergen Cyp c 2. In total, seven stable hybridoma cell lines producing MAbs of IgG class against recombinant common carp β-parvalbumin, β-enolase and natural Atlantic cod parvalbumin were produced by hybridoma technology. Using various immunoassays, the generated MAbs were shown to exhibit a broad cross-reactivity. They recognized both native and recombinant target allergens in muscle extracts of various fish species. Moreover, antibodies reacted with chicken and pork extracts. Using MAbs against fish parvalbumins, two variants of sandwich ELISA were developed and optimized to detect parvalbumins in fish extracts.